PENGARUH KARAKTERISTIK KOMITE AUDIT DAN REPUTASI KANTOR AKUNTAN PUBLIK (KAP) TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN MULTIFINANCE YANG TERCATAT DI BEI - NYAYU FADILAH FABIANY (Jurnal Manajemen Terapan dan Keuangan, 2016)
This study entitled "The Effect of Audit Committee Characteristics and Reputation Public Accounting Firm (KAP) of the Financial Reporting Time linessin the Multifinance Company Listedon the Stock Exchange". This studyis a survey researchby processing as econdary virginannual report published on the Indonesia Stock Exchange (IDX). The populationin this studyis afinance companythat is listed on the Stock Exchange 2011-2013. Samples taken during theperiod 2011-2013 amounted to 13 companies are selected based onthe intentand purpose of the study (purposive sampling). To determine the effect of Membership of the Audit Committee, member of Audit Committee Independence, Proportion Independent Commissioner, Competence, and Reputation Public Accounting Firm (KAP) the time linessof financial reporting by using logistic regression. The conclusion of this study that the Audit Committee, and Reputation Public Accounting Firm (KAP) with the same no significant effect onthe time liness offinancial reporting. Variable Membership of the Audit Committee, member of Audit Committee Independence, Proportion Independent Commissioner and Public Accounting Firm Reputationdoes not significantly influence the time liness offinancial reporting. While the competence variables significantly influence the time liness offinancial reporting.